A Simplified SARS-CoV-2 Mouse Model Demonstrates Protection by an Oral Replicon-Based mRNA Vaccine - Jawalagatti, Vijayakumar; Kirthika, Perumalraja; Hewawaduge, Chamith; Park, Ji-Young; Yang, Myeon-Sik; Oh, Byungkwan; So, Mi Young; Kim, Bumseok; Lee, John Hwa (Frontiers in Immunology, 2022)
A mouse model of SARS-CoV-2 that can be developed in any molecular biology lab with standard facilities will be valuable in evaluating drugs and vaccines. Here we present a simplified SARS-CoV-2 mouse model exploiting the rapid adenoviral purification method. Mice that are sensitive to SARS-CoV-2 infection were generated by transducing human angiotensin-converting enzyme 2 (hACE2) by an adenovirus. The expression kinetics of the hACE2 in transduced mice were assessed by immunohistochemistry, RT-PCR, and qPCR. Further, the ability of the hACE2 to support viral replication was determined in vitro and in vivo. The hACE2 expression in the lungs of mice was observed for at least nine days after transduction. The murine macrophages expressing hACE2 supported viral replication with detection of high viral titers. Next, in vivo studies were carried out to determine viral replication and lung disease following SARS-CoV-2 challenge. The model supported viral replication, and the challenged mouse developed lung disease characteristic of moderate interstitial pneumonia. Further, we illustrated the utility of the system by demonstrating protection using an oral mRNA vaccine. The design of multicistronic vaccine enabled by viral self-cleaving peptides encompasses the receptor binding domain (RBD, heptad repeat domain (HR), membrane (M) and epitopes of nsp13 of parental SARS-CoV-2. Further, Salmonella and Semliki Forest virus replicon were exploited respectively for gene delivery and mRNA expression. We recorded potent cross-protective neutralizing antibodies in immunized mice against the SARS-CoV-2 delta variant. The vaccine protected the mice against viral replication and SARS-CoV-2-induced weight loss and lung pathology. The findings support the suitability of the model for preclinical evaluation of anti-SARS-CoV-2 therapies and vaccines. In addition, the findings provide novel insights into mRNA vaccine design against infectious diseases not limiting to SARS-CoV-2.